Natural Disaster Management Synergy between Civilians-Indonesian Army (TNI AD) in Karo Regency - Agustatius Sitepu; Humaizi; Hamdani Harahap; Bengkel Ginting; Abd. Halim (International Journal of Educational Research Excellence (IJERE), 2023)
The Mount Sinabung eruption in Karo Regency, North Sumatra, several years ago resulted in substantial material losses and fatalities. The Karo Regency Government through the Regional Disaster Management Agency (BPBD) had tried to deal with disaster problems, especially the Mount Sinabung eruption, by involving the Indonesian Army (Kodim 0205/Tanah Karo). The method used in this study was qualitative with a case study approach and sample Army of Indonesia. The results indicated that there was synergy, in the civilian-military relation, in efforts to overcome the Mount Sinabung eruption; especially in terms of evacuation and handling disaster assistance in a better and more systematic way. Therefore, there was a necessity for synergy between the civilians-military as a form to reduce disaster risk, emergency response, and for recovery phase for communities affected by disasters.